The discourse organization of letters of complaint to editors in Philippine English and Singapore English - Ranosa-Madrunio, Marilu B. (Philippine Journal of Linguistics, 2004)
This paper presents an analysis of Philippine and Singaporean letters of complaint to editors published over a period of three months from July to August 2002. Eighty complaint letters from Philippine Daily Inquirer and The Straits Times, leading newspapers in the Philippines and Singapore, respectively, were examined in terms of their discourse structure. Textual analysis was used as a method of identifying the organizational moves. The t-test revealed that both Philippine and Singaporean samples employed the same number of moves: introduction, background, complaint, request for redress, suggestion, justification for suggestion, and conclusion. No significant differences were found in the frequency of occurrence of these moves except for introduction. However, a significant difference was found between the two samples as regards length of letters. It is then concluded that Philippine English and Singapore English do not differ at all in terms of discourse structure.